2014
DOI: 10.2478/s13382-014-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

Ambient ozone and emergency department visits due to lower respiratory condition

Abstract: Objectives: Ambient ozone (O 3 ) exposure is associated with a variety of health conditions. The objective of this study was to examine the effect of increased daily concentrations of ozone on emergency department (ED) visits due to lower respi ratory diseases (LRD), such as acute or chronic bronchitis, in Edmonton, Canada. Materials and Methods: Data concer ning 10 years (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) were obtained from 5 Edmonton hospital Emergency Departments. Odds ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In addition, a meta-analysis of 18 studies of PM 10 and exacerbations found a 10 μg/m 3 increase in daily PM 10 was associated with a 2.7% increase in COPD hospitalizations (29). The data linking air pollution with COPD exacerbations for O 3 is also convincing as higher O 3 concentrations have been shown to increase hospital and emergency department visits for lower respiratory disease, including COPD (3638). …”
Section: Copd Exacerbationsmentioning
confidence: 92%
“…In addition, a meta-analysis of 18 studies of PM 10 and exacerbations found a 10 μg/m 3 increase in daily PM 10 was associated with a 2.7% increase in COPD hospitalizations (29). The data linking air pollution with COPD exacerbations for O 3 is also convincing as higher O 3 concentrations have been shown to increase hospital and emergency department visits for lower respiratory disease, including COPD (3638). …”
Section: Copd Exacerbationsmentioning
confidence: 92%
“…1,2,[16][17][18][19] With specific regard to Windsor, Ontario, for 1 day lagged exposures in certain subgroups, Lavigne et al also reported statistically significant associations between ambient air pollution levels and emergency visits for asthma. 20 Exposure to ambient air pollution in Windsor increases the risk of ED visits for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report on O 3 to be associated with asthma 22,23,25,34,38 , acute and chronic bronchitis 39 , URTI 22 , and all respiratory visits 27,29,30,38 . Tamayo-Uria et al report that O 3 is negatively associated with COPD 28 .…”
Section: Discussionmentioning
confidence: 99%